High levels of patient satisfaction in joint uro-oncology clinics to assist patient choice in early prostate cancer and muscle-invasive bladder cancer - Kiltie, A; Southby, R; LeMonnier, K; Binnee, J; Niederer, J; Kartsonaki, C; Camilleri, P; Sabharwal, A; Brewster, S; Crew, J; Hamdy, F (Elsevier, 2018)
Multidisciplinary clinics are useful where there is patient choice, but patients are often seen sequentially, rather than synchronously in the same room. The National Institute for Health and Care Excellence (NICE) guidelines for bladder and prostate cancer [1,2] do not currently recommend using synchronous joint clinics.